2007
DOI: 10.1007/s11249-007-9237-6
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Evidence of Thermally Activated Friction with Polytetrafluoroethylene

Abstract: Under macroscopic pin-on-disk testing the sliding friction coefficient of Polytetrafluoroethylene (PTFE) was investigated over a temperature range of approximately 200-400 K. This study examines the nature of the temperature dependence by testing PTFE pins at varying temperature and humidity on a linear reciprocating pin-on-disk tribometer. The friction coefficient increased monotonically with decreasing temperature from l = 0.075to l = 0.210 in a manner consistent with thermal activation; it deviated from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
(36 reference statements)
6
27
0
Order By: Relevance
“…Michael et al [1], Theiler et al [2], and Hubner et al [3] compared results of ambient lab air testing with those of test submerged in cryogenic liquids and have shown either no trend or trends of reduced friction at cryogenic temperatures. Recent constant environment macroscale studies of various solid lubricants [4][5][6][7], and atomic-scale studies with terraces of graphite [8] show consistent trends of increased friction with decreased temperature, and the notion of thermally activated friction has been proposed [4,8,9]. Variable temperature experiments conducted on beds of aligned carbon nanotubes [10] and various high temperature polymer studies [11][12][13][14][15][16] have also demonstrated behavior that is well fit by an activated process at the macroscale.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Michael et al [1], Theiler et al [2], and Hubner et al [3] compared results of ambient lab air testing with those of test submerged in cryogenic liquids and have shown either no trend or trends of reduced friction at cryogenic temperatures. Recent constant environment macroscale studies of various solid lubricants [4][5][6][7], and atomic-scale studies with terraces of graphite [8] show consistent trends of increased friction with decreased temperature, and the notion of thermally activated friction has been proposed [4,8,9]. Variable temperature experiments conducted on beds of aligned carbon nanotubes [10] and various high temperature polymer studies [11][12][13][14][15][16] have also demonstrated behavior that is well fit by an activated process at the macroscale.…”
Section: Introductionmentioning
confidence: 78%
“…In systems that are low wear and thought to have interfacial sliding in macroscopic experiments monotonic temperature dependences in the direction of increasing friction coefficient with decreasing temperature have been observed. Fits to activation energy give values between 2 and 12 kJ/mol [4,5,10].…”
Section: Measurements Of Steady-state Wear Rates In Mos 2 Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The general hypothesis of thermally activated friction involves the notion that local potential barriers on contacting surfaces may be overcome thermally, thereby facilitating slippage [18,21]. A logical extension of this hypothesis suggests a reduction in friction with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%